Imperialist competitive algorithm for the flowshop problem - Minetti, Gabriela F. (2015)
This article presents a new optimization techniques based on Imperialistic Competitive Algorithm to solve the flowshop scheduling problems, which objective is to minimize the makespan. Furthermore, this approach is enhanced by a local search procedure in order to improve the best solutions. To show the efficiency of the proposed methods, we consider many instances of increasing complexity for the flowshop problem. Computational tests are presented and comparisons between the two approaches are made. The analysis of the results suggests that the enhanced approach is capable to find the best solutions of the problem at hand.